Highly efficient nitrogen removal of a coldness-resistant and low nutrient needed bacterium, Janthinobacterium sp. M-11. (May 2018) - Yang, Mo; Lu, Dongwei; Qin, Bida; Liu, Qianliang; Zhao, Yumeng; Liu, Huiling; Ma, Jun
Highlights: Coldness resistant microorganism, Janthinobacterium sp. M-11 was isolated from surface water. M-11 could remove ammonium, nitrite and nitrate at 2 °C. M-11 could remove N at low C/N ratio with a small inoculation. M-11 displayed different pathway of anaerobic denitrification from conversional aerobic denitrification bacteria. Denitrification genes of napA and narG were both found in M-11. Abstract: A novel heterotrophic nitrification-aerobic denitrification bacterium, identified as Janthinobacterium sp. M-11, was isolated from the Songhua River. When the initial ammonium concentration was 5 mg·L −1, 98% of ammonium was removed under cold condition (2 °C) with the C/N ratio of 5 at initial pH 7 and aerobic condition, which demonstrated the significant ammonium removal capacity of M-11 with low nutrient consumption at cold temperature. Denitrification processes under aerobic and anaerobic conditions were also investigated. 89% of nitrite and 89% of nitrate were removed under aerobic condition. Under anaerobic condition, 93% of nitrite and 98% of nitrate were removed. Interestingly, a high amount of nitrite accumulation was observed in the mid-stage of anaerobic denitrification for nitrate. This special phenomenon was probably because of the existence of narG gene amplified in the strain M-11, which would encode membrane-bound nitrate reductase and accelerate the nitrate conversion rate of M-11 under anaerobic condition.